Measuring Customer Satisfaction Using Multi-Criteria Analysis Model of Customer Satisfaction to Evaluate Product Lines (Case Study: Kaveh Glass Industrial Group) - Ali Yari , Maria; Modiri, Mahmoud; Khalili Damghani , Kaveh; Fathi Hafshjani , Kiamars (Journal of Information and Organizational Sciences, 2023)
Today, customer retention and growth is the first goal. Companies have taken a heavy toll on each customer, and competitors are constantly seeking to steal them. Satisfied customers have many benefits for the company, they are less sensitive to prices, will be a customer for a long period of time, and give a favorable view of the company and its products and services to others. Paying attention to the factors that are less important from the customer's point of view and evaluating these factors leads to spending resources in areas that have less impact on customer behavior, so understanding the factors that have the greatest impact on customer satisfaction to the organization to move in this will help. In this study, we intend to use the operational data of the lines and customer satisfaction scales to evaluate the relative efficiency of product lines using the network data envelopment analysis method. In order to achieve this goal and quantify the data obtained from the questionnaire, another linear programming method called multi-criteria satisfaction analysis will be used. Another innovation of this research is the application of customer expectations in the data envelopment analysis mole because most researchers that focus on quality do not consider this component in their evaluation model. The results indicate that the distribution system is the most effective factor and resources and supply is the most effective factor affecting customer satisfaction.